Notochordal Cells for Intervertebral Disc Regeneration: What is Their Most Effective Application?. (May 2014) - Potier, E.; de Vries, S.; Tryfonidou, M.; Ito, K.
Introduction: Intervertebral disc degeneration is one of the main causes of low back pain, a widespread disorder with tremendous socioeconomic impact. It is characterized by the inability of the resident cells (nucleus pulposus cells, NPCs) to maintain tissue homeostasis due to a change of phenotype and a decreasing number. Looking at development, the disc contains a second cell type, the notochordal cells (NCs), potential regulator, and/or progenitor of NPCs. As NCs are not present in adult humans, their potential for disc regeneration has been poorly explored. Few studies, however, showed that NCs can promote matrix synthesis of NPCs via soluble factors in conditioned medium (NCCM) 1 or direct coculture. 2 NCCM has also been shown to stimulate bone marrow stromal cells (BMSCs), 3 potential regenerative cells to complement the declining NPC population. It is, though, unclear what approach is the most effective to stimulate disc matrix production. The goal of this study was therefore to compare, in a simplified in vitro model, different approaches using NCs: (1) stimulation of NPCs with molecular factors secreted by NCs (NCCM) or direct coculture (NC); (2) addition of exogenous cells (BMSC), and (3) a combination of both molecular stimulation and exogenous cells (NCCM and BMSC). The effects on matrix production and cell phenotype were evaluated after 28 days of culture and compared with standard TGF-β stimulation. Materials and Methods: NPCs were extracted from caudal discs of cows (four independent donors pooled per repeat) and NCs from spinal discs of young pigs (one donor per repeat). BMSCs were isolated from bone marrow of calves (two independent donors pooled per repeat). All slaughterhouse materials were obtained in accordance with local regulations. NPCs and BMSCs alone were seeded at 3 million cells/mL in alginate beads. For cell mixture groups, NPCs and BMSCs (NPC + BMSC) and NPCs and NCs (NPC + NC) were mixed to a 1:1 ratio and seeded to a final concentration of 6 million cells/mL. All groups were cultured for 4 weeks in serum-free DMEM (Basal) at 5% O2, with four independent repeats for each group and condition. NPCs + BMSCs, BMSCs, and NPCs were also cultured in NCCM and chondrogenic medium (Chond; basal medium supplemented with TGFβ3 and dexamethasone). NCCM was produced by culturing porcine NPs rich in NCs in serum-free DMEM for 4 days under 5% O2 (one donor per repeat). At day 0/1 and 28, cell viability was evaluated by confocal imaging (calcein and propidium iodide staining), extracellular matrix composition by biochemical assays (DMMB, Hoechst dye and Chloramine-T assays for glycosaminoglycan [GAG], DNA and hydroxyproline (HYP) content, respectively), and gene expression profiles by RT-qPCR (for collagen types I and II, aggrecan, and SOX9). Statistical significance was evaluated with ANOVAs followed by a LSD-Fisher post hoc test. Statistical significance was assumed for p < 0.05 Results: Viable cells were observed in all groups at days 1 and 28. GAG and DNA contents increased when NPCs where exposed to NCCM, in levels similar to Chond medium (Fig. 1). Whereas addition of NCs had no effect on matrix production, addition of BMSCs led to improved GAG production (Fig. 1B). Cultured under NCCM, GAG, and DNA contents for NPC + BMSC also increased, but less than under Chond medium (Fig. 1). BMSCs alone displayed the same trends than NPC + BMSC, but with a less pronounced effect than of NCCM. Collagen production (HYP assay) was limited and only detected in groups containing BMSCs, with no effect of medium. Histology analysis confirmed the biochemical data. Gene expression of aggrecan, type II collagen, and SOX9 remained stable for all groups, except for BMSCs where their expression increased in time (4-145, 450 × day 0). For all groups, medium conditions had no effect on expression levels. Type I collagen expression did not vary. Conclusion: These results showed that molecular factors expressed by NCs (NCCM) are able to substantially stimulate both NPC's proliferation and GAG production. When NCs were directly added to NPCs (NPC + NC), however, no positive effects were observed. This lack of effect may be explained by a loss of the NC phenotype during the 4 weeks of culture, as shown before, 4 and suggests that the observed influence of NCCM may be intrinsic to freshly isolated NCs. Addition of BMSCs also had stimulatory effects. Though the BMSCs added were undifferentiated, the GAG/DNA was similar to NPCs alone, suggesting that either BMSCs became functional NPCs or that they stimulated GAG production by NPCs. BMSC's differentiation, however, is more likely as, cultured alone, BMSCs showed a high upregulation of several disc markers. NCCM combined with BMSCs, however, did not have an additive effect on GAG/DNA. As both NPCs and BMSCs alone responded well to NCCM, this suggests that the costimulation of BMSCs and NPCs in the NPC + BMSC groups make these cells less sensitive to any additional stimulation. To conclude, this study showed that NPCs can be substantially stimulated, and to a similar extent, by NCCM and coculture with BMSCs. The use of NCCM as a therapeutical approach, however, may be more attractive as it does not require the injection of a large number of cells (NPC:BMSC ratio 1:1 used). Moreover, its effect can be amplified using a higher concentration of NCCM, though the best approach will be to identify the molecular factor(s) involved in NCCM's effects. Acknowledgments This work was supported by AOSpine International through an AOSpine Research Network grant (SRN2011_11). Disclosure of Interest None declared References Abbott RD, Purmessur D, Monsey RD, Iatridis JC. Regenerative potential of TGFβ3?+?Dex and notochordal cell conditioned media on degenerated human intervertebral disc cells. J Orthop Res 2012;30(3):482–488 Aguiar DJ, Johnson SL, Oegema TR. Notochordal cells interact with nucleus pulposus cells: regulation of proteoglycan synthesis. Exp Cell Res 1999;246(1):129–137 Purmessur D, Schek RM, Abbott RD, Ballif BA, Godburn KE, Iatridis JC. Notochordal conditioned media from tissue increases proteoglycan accumulation and promotes a healthy nucleus pulposus phenotype in human mesenchymal stem cells. Arthritis Res Ther 2011;13(3):R81 Potier E, Ito K. Using notochordal cells of developmental origin to stimulate nucleus pulposus cells and bone marrow stromal cells for intervertebral disc regeneration. Eur Spine J 2014;23(3):679–688